Pengaruh Kurs Dollar Amerika Serikat, Inflasi, dan Harga terhadap Ekspor Kopi Provinsi Bali - ADIYASA, I KETUT AGUS; WIDHIANTHINI, WIDHIANTHINI; RANTAU, I KETUT (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2019)
The Effect of US Dollar, Inflation, and Price Exchange on Coffee Exports of BaliProvince Bali Province has one of the main export products from plantation products, namely coffee. Coffee contributes significantly to the volume of plantation exports from Bali Province. The fluctuating export volume of coffee commodities is influenced by the amount of production from the coffee itself. Exchange rates are a very influential factor in export activities. Another factor affecting the fluctuating export volume of coffee commodities is the inflation rate and the price of the export of coffee itself. The data used in this research was secondary data. The method of data collection was conducted by the method of documentation. Data is processed by the RCA index technique and multiple linear regression analysis which was previously equipped with the classic assumption test. The results of the RCA index test show that coffee commodities do not yet have competitiveness (RCA <1). The test results show that simultaneously, the US dollar exchange rate, inflation, and prices have a significant effect on the coffee exports of the Province of Bali. Partially the US dollar exchange rate has a positive and significant effect on coffee exports, inflation does not have a positive and significant effect on coffee exports, prices have a positive and significant effect on coffee exports in Bali Province.